Hadith #1065 - Sahih al-Bukhari - Amir bin Rabi'a bin Malik (Sahih al-Bukhari)
I saw the Prophet (ﷺ) on his Mount praying Nawafil by nodding his head, whatever direction he faced, but Allah’s Messenger (ﷺ) never did the same in offering the compulsory prayers.
Grade: Sahih

Hadith #1265 - Sahih al-Bukhari - Amir bin Rabi'a bin Malik (Sahih al-Bukhari)
The Prophet (ﷺ) said, “Whenever you see a funeral procession, stand up till the procession goes ahead of you.” Al-Humaidi added, “Till the coffin leaves you behind or is put down.”
Grade: Sahih

Hadith #1266 - Sahih al-Bukhari - Amir bin Rabi'a bin Malik (Sahih al-Bukhari)
The Prophet (ﷺ) said, “If any one of you see a funeral procession and he is not going along with it, then he should stand and remain standing till he gets behind it, or it leaves him behind, or the coffin is put down before it goes ahead of him . “
Grade: Sahih